Motor Competence and Physical Activity in Early Childhood: Stability and Relationship - Schmutz, Einat A.; Leeger-Aschmann, Claudia S.; Kakebeeke, Tanja H.; Zysset, Annina E.; Messerli-Bürgy, Nadine; Stülb, Kerstin; Arhab, Amar; Meyer, Andrea H.; Munsch, Simone; Puder, Jardena J.; Jenni, Oskar G.; Kriemler, Susi (Frontiers in Public Health, 2020)
Background Normal motor development and adequate levels of engagement in physical activity during the early years of life form the foundation of long-term psychological and physiological health. This is one of the very few studies that investigate the stability and relationships of motor competence and physical activity in preschool children. Methods Baseline and 12-month follow-up data of 550 preschool children aged 2 to 6 years from the Swiss Preschoolers’ Health Study were used for this work. Physical activity data, expressed in counts per minute for total physical activity and minutes per day for time spent moderately-to-vigorously physically active, was collected over one week using accelerometers. Motor competence was assessed with the Zurich Neuromotor Assessment. Both motor competence and physical activity were age- and sex-adjusted. To examine the individual stability of physical activity and motor competence and reciprocal cross-sectional and longitudinal effects between these two domains, a latent variable cross-lagged panel model where motor competence was represented through a latent construct was examined using structural equation modeling. Results A weak cross-sectional correlation of motor competence with total physical activity (r = .24) and moderate-to-vigorous physical activity (r = .23) was found. Motor competence exhibited high stability (β = .82) in the preschool years and physical activity was moderately stable with estimates ranging from β = .37 for total physical activity to β = .48 for moderate-to-vigorous physical activity. In contrast to the autoregressive coefficients denoting individual stability, both cross-lagged effects were negligible indicating that physical activity was not a determinant of motor competence or vice versa. Conclusions Motor competence and physical activity developed independently of each other in early childhood. Although measures of quantity and intensity of physical activity were not related to motor development, specific movement experiences and practice – which are not reflected by accelerometry – may be needed for skill development. Future research should focus on examining what type of physical activity is important for motor development and how to assess it, and also whether the relationship between physical activity and motor competence evolves over time.